Millable-type fluorosilicone rubber composition and rubber component for use around transport vehicle engine

JP2025029315APending Publication Date: 2025-03-06SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023133864
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-03-06

AI Technical Summary

Benefits of technology

【0013】 本発明のミラブル型フロロシリコーンゴム組成物は、アミン系老化防止剤等に接触しても物性低下が少なく、耐熱性が良好なフロロシリコーンゴム成形品(硬化物)を与えるものであって、該フロロシリコーンゴム成形品は、特に、輸送機のエンジン周辺用ゴム部品等の用途に好適に使用できるものである。又、PFOSなどのパーフルオロアルキル基含有化合物が規制されたため、長鎖のフロロアルキル基はフロロシリコーンゴムの変性基として使用できなくなったが、本発明の該フロロシリコーンゴム成形品であれば環境に負荷を与えることもなく、その規制の対象にもならない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029315000001
    Figure 2025029315000001
  • Figure 2025029315000002
    Figure 2025029315000002
  • Figure 2025029315000003
    Figure 2025029315000003
Patent Text Reader

Abstract

To provide a millable-type fluorosilicone rubber composition that yields a cured product with superior amine resistance and heat resistance.SOLUTION: A millable-type fluorosilicone rubber composition comprises (A) raw rubber-like organopolysiloxane represented by the formula (where R1 independently represents a group selected from a C1-10 alkyl group, a C6-10 aryl group, and a C7-10 aralkyl group; R2 represents a C2-8 alkenyl group; a and b each represent an integer of 1 or more; c represents an integer of 0 or more; a+b+c=2,000-6,000; and a / (a+b+c)=0.3-0.8): 100 pts.mass, (B) reinforcing silica with a BET-based specific surface area of 50 m2 / g or more: 10-100 pts.mass, and (C) organic peroxide: catalytic amount.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a millable-type fluorosilicone rubber composition and to rubber parts for use around transport engines, which are made of a cured product of said fluorosilicone rubber composition. [Background technology]

[0002] Fluorosilicone rubber compositions, which are based on fluorosilicone rubber having 3,3,3-trifluoropropyl groups as side-chain substituents, exhibit excellent solvent resistance in addition to the properties of dimethylsilicone rubber, and are therefore widely used in transportation equipment parts and petroleum-related equipment parts such as diaphragms, O-rings, and oil seal materials. On the other hand, amines such as various polyether amines, alcohol amines, and alkyl amines are added to gasoline fuels and oils as antioxidants and rust inhibitors. Although fluorosilicone rubber has excellent solvent resistance, the siloxane main chain cracks when exposed to these amines. Therefore, even with fluorosilicone rubber, the initial physical properties of the molded product cannot be maintained.

[0003] As a countermeasure, Patent Document 1 lists a method of preventing deterioration caused by antioxidants by adding an anti-extraction buffer to fluorosilicone rubber. In addition, Patent Document 2 improves fuel oil resistance by using an organopolysiloxane containing a perfluoroalkyl ether group having 4 or more carbon atoms as a base polymer. In addition, Patent Document 3 attempts to improve alcohol fuel oil resistance by adding titanium dioxide and triallyl isocyanurate having an average particle size of 0.1 to 1.0 μm to a fluorosilicone polymer having an unsaturated group at at least one end. Furthermore, Patent Document 4 attempts to improve amine resistance by adding at least one chloride selected from alkali metal chlorides, alkaline earth metal chlorides, and ammonium chloride to a fluorosilicone rubber composition.

[0004] However, even with these methods, it has been difficult to sufficiently prevent cracking of fluorosilicone rubber when it comes into contact with amines.

[0005] In recent years, the Ministry of the Environment has placed organic fluorine compounds on the list of "items to be monitored for the protection of human health." As a result, compounds containing perfluoroalkyl groups such as PFOS have been restricted, and long-chain fluoroalkyl groups can no longer be used as modifying groups in fluorosilicone rubber. As a result, alternative materials are being sought. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 7-252421 [Patent Document 2] Japanese Patent Application Publication No. 5-186700 [Patent Document 3] JP 2000-26735 A [Patent Document 4] JP 2017-222796 A Summary of the Invention [Problem to be solved by the invention]

[0007] The object of the present invention is to provide a millable-type fluorosilicone rubber composition which gives a fluorosilicone rubber (cured product) which exhibits little deterioration in physical properties and good heat resistance even when it comes into contact with amine-based antioxidants, etc. contained in fuel, and to provide rubber parts for use around the engine of a transport aircraft which are made of the cured fluorosilicone rubber.

[0008] In addition, a millable composition refers to a composition that is non-liquid (paste or solid) with no self-fluidity at room temperature (25°C) and can be mixed uniformly under shear stress using a kneading means such as a roll mill. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides (A) The following formula (1) [ka] (In the formula, R 1 are independently selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms; R 2 is an alkenyl group having 2 to 8 carbon atoms, a and b are each an integer of 1 or more, c is an integer of 0 or more, a+b+c=2,000 to 6,000, and a / (a+b+c)=0.3 to 0.8. The siloxane units bounded by a, b, and c may be bonded in a block or random manner. 100 parts by mass of a raw rubber-like organopolysiloxane represented by the formula: (B) The specific surface area by the BET method is 50 m 2 / g or more reinforcing silica: 10 to 100 parts by mass, (C) Organic peroxide: catalytic amount, The present invention provides a millable type fluorosilicone rubber composition comprising:

[0010] The millable type fluorosilicone rubber composition of the present invention is able to give fluorosilicone rubber molded articles (cured products) that exhibit little deterioration in physical properties even when in contact with amine-based antioxidants and have good heat resistance.

[0011] The present invention also provides a rubber part for use around the engine of a transport aircraft, which is made of a cured product of the above-mentioned millable-type fluorosilicone rubber composition.

[0012] Rubber parts for use around transport engines made from a cured product of the millable-type fluorosilicone rubber composition of the present invention are preferred because they experience little deterioration in physical properties even when in contact with amine-based antioxidants contained in gasoline fuels and oils. Effect of the Invention

[0013] The millable-type fluorosilicone rubber composition of the present invention gives a fluorosilicone rubber molded article (cured product) that exhibits little deterioration in physical properties even when in contact with amine-based antioxidants and the like, and has good heat resistance, and the fluorosilicone rubber molded article is particularly suitable for use in rubber parts around transport engines, etc. Furthermore, since perfluoroalkyl group-containing compounds such as PFOS have been restricted, long-chain fluoroalkyl groups can no longer be used as modifying groups in fluorosilicone rubber, but the fluorosilicone rubber molded article of the present invention does not impose a burden on the environment and is not subject to such restrictions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention was made to solve the above problems. The inventors discovered that by having trifluoroethoxypropyl groups in the siloxane units instead of the 3,3,3-trifluoropropylmethylsiloxane units that make up the main chain of the fluorosilicone polymer, the deterioration of the physical properties of the fluorosilicone rubber due to contact with amine-based antioxidants, etc., can be suppressed, which led to the creation of the present invention.

[0015] The present invention will be described in detail below, but the present invention is not limited thereto.

[0016] [Component (A)] In the present invention, component (A) is a main component in a millable type silicone rubber composition, The following formula (1) [ka] (In the formula, R 1 are independently selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms; R 2is an alkenyl group having 2 to 8 carbon atoms, a and b are each an integer of 1 or more, c is an integer of 0 or more, a+b+c=2,000 to 6,000, and a / (a+b+c)=0.3 to 0.8. The siloxane units bounded by a, b, and c may be bonded in a block or random manner.

[0017] In addition, raw rubber refers to a high polymer that is either a very viscous liquid at room temperature (25° C.) or a non-liquid (paste or solid) that has no self-flowing property.

[0018] In the above formula (1), R 1 are independently selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, each of which preferably has 8 or less carbon atoms, and specific examples thereof include alkyl groups such as methyl, ethyl, isopropyl, and butyl groups, cycloalkyl groups such as cyclohexyl and cyclopentyl groups, aryl groups such as phenyl, tolyl, and xylyl groups, and aralkyl groups such as benzyl and phenylethyl groups. Particularly preferred groups in the present invention are methyl, ethyl, and phenyl groups. R is an alkenyl group having 2 to 8 carbon atoms. 2 Examples of the alkyl group include a vinyl group and an allyl group, and the vinyl group is particularly preferred.

[0019] Furthermore, in the formula (1), a and b are each an integer of 1 or more, c is an integer of 0 or more, a+b+c=2,000 to 6,000, and a / (a+b+c)=0.3 to 0.8.

[0020] If a+b+c is less than 2,000, the viscosity will be low and the stickiness will increase, significantly impairing the workability of the Millable Rubber. Conversely, if it exceeds 6,000, the viscosity will be high and subsequent additions and blending will be difficult.

[0021] Furthermore, a / (a+b+c) is 0.3 to 0.8, and preferably 0.3 to 0.7. If it is less than 0.3, sufficient oil resistance cannot be obtained. If it exceeds 0.8, the flexibility of the cured product may decrease, and the tensile strength, tear strength, and elongation at break may become insufficient.

[0022] Furthermore, b / (a+b+c)=0.1 to 0.3 is preferable. If it is 0.1 or more, crosslinking will proceed sufficiently and the product will have sufficient hardness and heat resistance. If it is 0.3 or less, the cured product will not become brittle.

[0023] In this organopolysiloxane, R is an alkenyl group having 2 to 8 carbon atoms. 2 Each molecule may have three or more alkenyl groups, and the content of these groups is preferably 0.01 to 1 mol %, particularly preferably 0.02 to 0.5 mol %, relative to the number of silicon atoms in the molecule. The alkenyl group is particularly preferably a vinyl group. If the alkenyl group content is 1 mol % or less, the rubber hardness becomes appropriate, the rubber does not become brittle, and mechanical strength such as tensile strength and tear strength becomes sufficient.

[0024] The organopolysiloxane represented by the above formula (1) can be prepared, for example, from a compound represented by the following formula (2): [ka] The siloxane oligomer represented by the formula (I) can be obtained by ring-opening polymerization of trifluoroethoxypropylsiloxane cyclic trimer using a siloxane oligomer represented by the formula (I) as an initiator. Specifically, the polymerization is carried out by adding an appropriate amount of the above-mentioned siloxane oligomer to a cyclic organosiloxane and carrying out living polymerization under a closed condition at 100°C to 150°C. By adjusting the amount of the above-mentioned siloxane oligomer during the living polymerization, an organopolysiloxane having reached the desired degree of polymerization can be obtained.

[0025] The degree of polymerization of the organopolysiloxane is 2,000 to 6,000, preferably 2,000 to 5,500, and particularly preferably 2,000 to 5,000. It is characterized by being a so-called raw rubber-like substance with no self-flowing property at room temperature (25°C). If the degree of polymerization is less than 2,000, the viscosity becomes low and the stickiness increases, significantly impairing the processability of the millable rubber. On the other hand, if it exceeds 6,000, the viscosity becomes high and subsequent addition and blending becomes difficult. The degree of polymerization in the present invention is determined as the weight-average degree of polymerization from the weight-average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC) analysis under the following conditions.

[0026] [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (0.5 wt% THF solution)

[0027] The component (A) may be a single type, or a mixture of two or more types differing in molecular weight (degree of polymerization) or molecular structure.

[0028] In the present invention, because a crude rubber-like organopolysiloxane having D units substituted with trifluoroethoxypropyl groups is used as the base polymer, it is possible to provide a fluorosilicone rubber that is not subject to regulations on perfluoroalkyl group-containing compounds, is less likely to crack even when in contact with amine-based antioxidants, and is able to sufficiently maintain its physical properties and have good heat resistance.

[0029] [(B) Component] The reinforcing silica of component (B) acts as a component that imparts excellent mechanical properties to the resulting millable fluorosilicone rubber composition. The reinforcing silica may be either precipitated silica (wet silica) or fumed silica (dry silica). In the present invention, the reinforcing silica of component (B) has a specific surface area of ​​50 m2 or less as measured by the BET method. 2 / g or more, and preferably 100 to 400m 2 / g. This specific surface area is 50m 2 If the viscosity is less than 400m / g, the reinforcing effect of component (B) will be insufficient. 2 If the viscosity is not more than 1000g / g, the viscosity will not be too high, and there is no risk of the moldability decreasing, which is preferable.

[0030] The reinforcing silica of component (B) is preferably surface-treated, and may be surface-treated with an organosilicon compound such as organopolysiloxane, organopolysilazane, chlorosilane, or alkoxysilane containing a silanol group. The timing of the surface treatment is arbitrary, and it is sufficient that the treatment is completed before the silicone rubber composition is obtained. The surface-treated reinforcing silica may be one that has been previously treated, or one that has been treated on the spot by adding a surface treatment agent to untreated silica when producing the silicone rubber composition. These reinforcing silicas may be used alone or in combination of two or more.

[0031] The amount of reinforcing silica (B) added is 10 to 100 parts by mass, preferably 15 to 80 parts by mass, and more preferably 20 to 70 parts by mass, per 100 parts by mass of the organopolysiloxane (A). If the amount added is outside the above range, not only will the processability of the silicone rubber composition decrease, but the mechanical properties of the cured silicone rubber will also be insufficient.

[0032] [(C) component] The organic peroxide of component (C) is a curing agent, and is not particularly limited as long as it can cure component (A). Examples of organic peroxides include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, p-methylbenzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, and 1,6-hexanediol-bis-t-butylperoxycarbonate.

[0033] The amount of organic peroxide blended is a catalytic amount relative to 100 parts by mass of component (A), and is preferably 0.1 to 10 parts by mass, and more preferably 0.2 to 5 parts by mass. When the amount blended is 0.1 part by mass or more relative to 100 parts by mass of component (A), curing is sufficient, and when the amount blended is 10 parts by mass or less, discoloration of the cured silicone rubber due to decomposition residues of the organic peroxide is not caused.

[0034] [Other ingredients] In addition to the above-mentioned components, the millable fluorosilicone rubber composition of the present invention can optionally contain, as necessary, fillers such as crushed quartz, crystalline silica, diatomaceous earth, calcium carbonate, etc., colorants, tear strength improvers, acid acceptors, thermal conductivity improvers such as alumina and boron nitride, release agents, and filler dispersants such as various alkoxysilanes, particularly phenyl-containing alkoxysilanes and their hydrolysates, diphenylsilanediol, carbon functional silane, and other fillers and additives known in thermosetting silicone rubber compositions.

[0035] [Method of producing the composition] The millable type fluorosilicone rubber composition of the present invention can be obtained by mixing the components constituting the composition using a known mixer such as a kneader, a Banbury mixer, a twin roll mixer, etc. When using a composition containing the above-mentioned components (A) to (C) as the millable type fluorosilicone rubber composition, it is preferable to first mix components (A) and (B) to obtain a mixture, and then add component (C) to the mixture.

[0036] When the composition containing the components (A) to (C) further contains other components, it is preferable to first mix the components (A), (B), and the other components to obtain a mixture, and then add the component (C) to the mixture.

[0037] When using surface-treated reinforcing silica as component (B), it may be mixed as it is, but when the surface of component (B) is treated later, the timing is optional. For example, a separate surface treatment step may be provided, or the component (B), other components such as component (A) (all or part of it), and a surface treatment agent may be mixed, and the mixture may be heated as necessary while being mixed to perform surface treatment.

[0038] In this specification, the kneaded product prior to the addition of component (C) is sometimes referred to as the silicone base compound, and the millable-type fluorosilicone rubber composition after the addition of component (C) is sometimes referred to as the full compound.

[0039] [Curing conditions] The millable type fluorosilicone rubber composition of the present invention can be cured by a known curing method under known curing conditions. Specifically, the composition can be cured by heating at a temperature of usually 25 to 200° C., preferably 80 to 160° C. The heating time may be about 0.5 minutes to 5 hours, and particularly about 1 minute to 3 hours. The millable type fluorosilicone rubber composition of the present invention may be cured under pressure.

[0040] [Cured product] As described above, the composition of the present invention can be cured to obtain a cured product. This cured product gives a fluorosilicone rubber molded product (cured product) that exhibits little deterioration in physical properties and good heat resistance even when in contact with amine-based antioxidants, etc. The cured product of the composition of the present invention is suitable for rubber parts for use in the vicinity of transport engines. Rubber parts for use in the vicinity of transport engines made of such a cured product are preferred because they are less susceptible to deterioration in physical properties even when they come into contact with amine-based antioxidants contained in gasoline fuels, oils, etc. EXAMPLES

[0041] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.

[0042] [Heat resistance] Using the cured product of the millable type fluorosilicone rubber composition prepared in the following examples and comparative examples, a test sheet was prepared according to JIS K 6249:2003, and the initial values ​​of hardness, tensile strength (MPa), and elongation at break (%) were measured using this. In addition, the test sheet was placed in a dryer at 200°C for 72 hours (3 days), and then the hardness, tensile strength (MPa), and elongation at break (%) were similarly measured. In addition, the change rate of Duro A hardness and the change rate (decrease rate) of elongation at break were calculated from the measured values ​​using the following formula. In addition, in the present invention, the hardness is a value measured using a durometer A hardness tester.

[0043] Hardness change rate = {(Hardness after heating at 225°C for 72 hours) - (Initial hardness)} / (Initial hardness) x 100(%) Tensile strength change rate = {(initial tensile strength) - (tensile strength after heating at 225°C for 72 hours)} / (initial elongation at break) x 100 (%) Change in elongation at break = {(initial elongation at break) - (elongation at break after heating at 225°C for 72 hours)} / (initial elongation at break) x 100(%)

[0044] [Oil resistance measurement] The hardness and initial volume change rate (%) of the cured products of the millable type fluorosilicone rubber compositions prepared in the following examples and comparative examples were measured in accordance with JIS K 6249:2003. The test sheets were immersed in IRM903 (manufactured by Japan San Oil) at 150°C for 70 hours, after which the hardness and volume change rate were measured. The results are shown in Table 1.

[0045] [Amine resistance measurement] For the millable type fluorosilicone rubber compositions prepared in the following examples and comparative examples, the obtained full compounds were pressure molded at 165°C for 10 minutes, cured, and then post-cured at 200°C for 4 hours to prepare small cylindrical test pieces for measuring compression set with a diameter of 13 mm and a height of 6.3 mm. The measurement method was based on JIS K 6262:2013 to measure the initial value of compression set. The test pieces were immersed at room temperature for 168 hours at 120°C in a 1% by mass IRM903 solution of N,N'-di-sec-butyl-p-phenylenediamine or a 10% ethanol solution of N,N'-bis(salicylidene)-1,2-propanediamine in a 25% compressed state, and then cooled to measure the compression set.

[0046] The following components were used as component (A): (A-1): Organopolysiloxane raw rubber represented by the following formula, having 18 vinyl groups in one molecule, 0.44 mol% relative to the number of silicon atoms in the molecule, and an average degree of polymerization of 4,018. [ka]

[0047] (A-2): Organopolysiloxane raw rubber having the following formula, the number of vinyl groups in one molecule being 18 (0.45 mol % relative to the number of silicon atoms in the molecule), and an average degree of polymerization of 4,033. [ka]

[0048] The following components were used as component (B): (B):Specific surface area 130m 2 / g of dry silica (manufactured by Nippon Aerosil Co., Ltd., product name: Aerosil 130)

[0049] The following components were used as component (C): (C) 2,5-Dimethyl-2,5-di(t-butylperoxy)hexane

[0050] [Example 1] 40 parts by mass of component (B) and 10 parts by mass of diphenylsilanediol as a surface treatment agent for component (B) were added to 100 parts by mass of component (A-1), and the mixture was uniformly kneaded with a two-roll mill, heat-treated at 150°C for 4 hours, and then mixed and plasticized with a two-roll mill to obtain silicone base compound A1 as the base. 0.8 parts by mass of paste containing 80% by mass of component (C) (corresponding to 0.64 parts by mass of component (C) relative to 100 parts by mass of component (A-1)) was added to 100 parts by mass of the obtained base compound, and the mixture was uniformly mixed with a two-roll mill to obtain a full compound. Test sheets and cured products were prepared from the obtained composition, and various physical properties were evaluated. The results are shown in Table 1.

[0051] [Example 2] 40 parts by mass of component (B) and 10 parts by mass of diphenylsilanediol as a surface treatment agent for component (B) were added to 100 parts by mass of component (A-2) and uniformly kneaded, heat treated at 150°C for 4 hours, and then mixed and plasticized with a two-roll mill to obtain silicone base compound A2 as the base. 0.8 parts by mass of paste containing 80% by mass of component (C) (corresponding to 0.64 parts by mass of component (C) relative to 100 parts by mass of component (A-1)) was added to 100 parts by mass of the obtained base compound, and the mixture was uniformly mixed with a two-roll mill to obtain a full compound. Test sheets and cured products were prepared from the obtained composition, and various physical properties were evaluated. The results are shown in Table 1.

[0052] [Comparative Example 1] In Example 1, the (A-1) component was replaced with organopolysiloxane raw rubber (A-3) consisting of 99.85 mol% dimethylsiloxane unit, 0.125 mol% methylvinylsiloxane unit, and 0.025 mol% dimethylvinylsiloxy unit (number of vinyl groups in one molecule: 10, 0.15 mol% relative to the number of silicon atoms in the molecule), with an average degree of polymerization of 6,000, and 10 parts by mass of diphenylsilanediol was added as a dispersant and uniformly kneaded, heat treated at 150°C for 4 hours, and then beaten and plasticized with a two-roll mill to obtain a silicone base compound A3 as the base. Thereafter, a silicone rubber composition was prepared in the same manner, and test sheets and cured products were produced from the obtained compositions, and various physical properties were evaluated. The results are shown in Table 1.

[0053] [Comparative Example 2] In Example 1, the (A-1) component was replaced with the following organopolysiloxane raw rubber (A-4) having 16 vinyl groups per molecule, 0.395 mol% relative to the number of silicon atoms in the molecule, and an average degree of polymerization of 4,023, and 10 parts by mass of diphenylsilanediol was added as a dispersant and uniformly kneaded, and the mixture was heat-treated at 150°C for 4 hours, and then beaten and plasticized with a two-roll mill to obtain the silicone base compound A4 as the base. Thereafter, silicone rubber compositions were prepared in the same manner, and test sheets and cured products were produced from the obtained compositions, and various physical properties were evaluated. The results are shown in Table 1. [ka]

[0054] [Comparative Example 3] In Example 1, the component (A-1) was replaced with an organopolysiloxane raw rubber (A-5) having the following formula: the number of vinyl groups in one molecule: 18 (0.30 mol % relative to the number of silicon atoms in the molecule) and an average degree of polymerization of 5990. [ka] The mixture was mixed uniformly with 10 parts by mass of diphenylsilanediol added as a dispersant, heat treated at 150°C for 4 hours, and then beaten and plasticized using a two-roll mill to obtain the base silicone base compound A5. Silicone rubber compositions were then prepared in the same manner, and test sheets and cured products were made from the resulting compositions, and various physical properties were evaluated. The results are shown in Table 1.

[0055] [Table 1]

[0056] In the heat resistance measurement, Examples 1 and 2 were superior to the Comparative Examples in all respects except for the hardness change. In the oil resistance measurement, Examples 1 and 2 were superior to the Comparative Examples in all respects except for the volume change rate. In terms of the compression set measured for the oil resistance and amine resistance, Examples 1 and 2 were better than each of the Comparative Examples. Comparative Examples 2 and 3, which were equivalent in terms of hardness change and volume change rate, were significantly inferior to the Examples in the measurement of compression set after immersion in a 1 mass % IRM903 solution of N,N'-di-sec-butyl-p-phenylenediamine. That is, it is clear that Examples 1 and 2 are superior to the Comparative Example in amine resistance, and achieve excellent heat resistance, oil resistance, and amine resistance all at the same time.

[0057] The present invention is not limited to the above-mentioned examples. The above-mentioned embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. (A) Formula (1) below 【Chemistry 1】 (In the formula, R 1 are independently selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms; R 2 is an alkenyl group having 2 to 8 carbon atoms, a and b are each an integer of 1 or more, c is an integer of 0 or more, a+b+c=2,000 to 6,000, and a / (a+b+c)=0.3 to 0.

8. The bonds of the siloxane units bounded by a, b, and c may be block or random. Raw rubber-like organopolysiloxane represented by the formula: 100 parts by mass, (B) A material with a specific surface area of ​​50 m2 measured by the BET method 2 / g or more reinforcing silica: 10 to 100 parts by mass, (C) Organic peroxide: catalytic amount, A millable type fluorosilicone rubber composition comprising:

2. 2. A rubber part for use around the engine of a transport aircraft, comprising a cured product of the millable type fluorosilicone rubber composition according to claim 1.

Citation Information

Patent Citations

  • Silicone rubber composition

    JP1992025563A

  • Oil-resistant silicone rubber composition

    JP1994107952A

  • Fluorine-containing organic silicon compound

    JP1997124663A

  • Fluorosilicone rubber composition

    JP2015113456A

  • Fluorosilicone rubber composition and rubber component used around engine of transport

    JP2016056315A